ANALYSIS OF BIRD DIVERSITY AND FEEDING GUILDS IN THE SIMPANG RUSA ECOSYSTEM RECOVERY AREA, SUSUKAN BARU RESORT, WAY KAMBAS NATIONAL PARK - Iswandaru, Dian; Nurazizah, Wianda Pipit; Rohman, Fatur; Rahma Fitriana, Yulia (Jurnal Belantara, 2025)
The presence of birds can indicate whether the environment supports the life of an organism or not because it has a reciprocal and interdependent relationship with its environment. The diversity and abundance of bird species can indicate how the area is doing. This study aimed to determine birds' diversity, richness, evenness, dominance, feeding groups, and conservation status in the Simpang Rusa Ecosystem Recovery Area (SRERA). Data collection was done by direct observation in the field using the point count method. A total of 47 bird species from 24 families with a species diversity value (H') of 3.11 in the high category, species richness value (R) 7.62, species evenness value (E) of 0.8 in the good category, and species dominance (C) of 0.07 in the low category. 6 feeding groups were identified, namely insect eaters (53%), fruit eaters (18%), animal material eaters (12%), fish eaters (7%), seed eaters (6%) and nectar eaters (3%). Four protected bird species were found, namely Elanus caeruleus and Spilornis cheela, Gorsachius melanolophus and Rhipidura javanica. Based on the IUCN Redlist, there are two bird species with Near Treatened status, namely the Phaenicophaeus diardi and Cyornis turcosus, one species with Vulnerable status, namely the Acridotheres javanicus, and 42 other species with Least Concern status. Based on CITES, two bird species have Appendix II status. Annual monitoring is needed to monitor the population and mitigate threats as a conservation effort.